The Importance of Husband Support During Childbirth in Indonesia - Mohammad Fais Satrianegera; Veni Hadju; Yessy Kurniati (Al-Sihah : The Public Health Science Journal, 2021)
The Assistance of the husband during the delivery of the wife makes the process smoother. The assistance was related to various factors, including husband support. This study aims to determine the relationship between husband support and wife delivery assistance at the Sheikh Yusuf General Hospital in Gowa Regency. The study was conducted from October-November 2019. This study used a cross-sectional approach the population is all husbands who came to bring their wives in the period of October-November amounted to 385 people. The research sample was obtained by simple random sampling totaling 134 people. Data analysis was performed using SPSS with a chi-square test where the significance value was p <0.05. The results showed that the respondents in this study were mostly aged 18-24 years as many as 39.6%, the last level of education was Senior High School as much as 51.5% and working as entrepreneurs 38.8%. A small proportion of respondents in this study aged 39-45 years were 4 (3.0%), D3 education level was 4 (3.0%), and worked as a repairman 3 (2.2%). The study also showed that there were 81.3% of husbands supported childbirth and 18.7% did not. In addition, there were 64.9% of husbands accompanied their wives at delivery, and 35.1% did not accompany them. There is a relationship between the husband's support and delivery assistance (p = 0.008). It is expected that the husband can play an active role in assisting his wife so that it helps the smooth delivery process